E-LEARNING CHALLENGES IN POLAND DURING THE COVID-19 PANDEMIC - Agieszka Parlińska (Polityki Europejskie, Finanse i Marketing)
The main objective of the paper is to show the new challenges for education that arose inPoland from 2019-2021, and the use of e-learning methods. This new approach, and the purposeand added value of this study, is to enrich the knowledge of the use of new teaching and researchmethods gained during the Covid-19 pandemic and applicability to pandemics generally, as wellas continued use of these methods afterwards..To achieve the objective, the method of literature analysis and critique was used, as well as aratio analysis based on historical data from Statistics Poland (GUS), EUROSTAT and the author’sown first-hand observations as a university educator.The research results helped to formulate several conclusions regarding the factors whichinfluence effective e-learning, such as: internet access and quality; the availability of adequatesoftware, hardware and other tools; and the digital competence of teachers and students. A shortSWOT analyse is also presented to highlight key considerations that are crucial for the future of elearning.